Spread of the alien bleak Alburnus alburnus (Linnaeus, 1758) (Actinopterygii cyprinidae) in the Iberian Peninsula: The role of reservoirs - Vinyoles, Dolors (2012)
Since its first record in a tributary of the Ebro basin in 1992, the bleak Alburnus alburnus has spread to almost the whole Iberian Peninsula. In this paper (based on electrofishing surveys in 598 localities), we provide information on the expansion of the bleak. We detail current distribution in the Ebro basin and the rivers of the Eastern Pyrenees and we report its presence in three other major Iberian drainages. Currently, the bleak is sympatric with 15 Iberian endemic species (58% of total Iberian endemic fish). The possible threats to the rich Iberian ichthyofauna caused by the presence of the bleak are discussed. The factors that promoted the extremely rapid expansion of this exotic cyprinid are examined, focusing on the role of reservoirs, which seem to favour its dispersal.